SISTEM INFORMASI PELAYANAN ADMINISTRASI BERBASIS WEBSITE PADA LEMBAGA KURSUS DAN PELATIHAN (LKP) AMIKOM PALEMBANG - Iin Seprina; Ririn Shintia Wati (JURNAL ILMIAH BETRIK, 2023)
Abstract: Website-based information systems are developing rapidly at the moment, both in terms of promotion and administrative processing. LKP AMIKOM is a company that operates in the service sector by providing computer education and training courses. The administrative process for Course and Training Institutions (LKP) is important in the smooth implementation of training programs. Currently, the training registration process for prospective course participants is still manual by coming directly to the institution and then being given a registration form and prospective participants filling out the registration form completely. and recording training data in the AMIKOM LKP using the help of Microsoft Word and Microsoft Excel. However, in its use, several obstacles were still found, such as repetitive data input and AMIKOM LKP report data spread across various files. So that prospective training participants have difficulty registering for training programs and looking for information about the type of training that will take place and the information disseminated is also limited to people who are really looking for and need a training place or course. Therefore, a new system is needed to overcome this problem, which can help make it easier to register for training and can manage other training supporting data. The method used in making this application program is the Rapid Application Development (RAD) method which occurs into several phases or stages, namely the Requirements Planning stage, the System Design process stage, the development and feedback collection process stage and the Implementation stage. Using the PHP programming language and utilizing a database MYSQL as database server. With this system, it is hoped that it can be implemented by LKP AMIKOM so that it can help and improve the performance of staff, especially those who handle the computer course registration process and can make it easier for LKP AMIKOM to tidy up the storage of documents that are computerized and easy to access because they are web-based.